ARTIKEL REVIEW: STUDI FITOKIMIA DAN FARMAKOLOGI PARIJOTO (Medinilla magnifica) - Rifqi Maulana Toni.S; Marhani Apriana; Muhammad Choerul Huda; Muhammad Choerul Kamal; Allahuddin; Retna Ayu Septiani; Sayyid Rafli Ash-shidiqi; Fera Anggraeni (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Health problems are one of the most complex problems, the sanitation process in improving health with various uses of plants in the State of Indonesia. A country that will be rich in natural resources. As a form of serious treatment that improves health from various diseases in Indonesia, called by utilizing Parijoto fruit (Medinilla magnifica) by utilizing the active substances contained in the fruit in the form of flavonoids, tannins, saponins and alkaloids through in vitro and in vitro tests. In vitro which has important properties in the treatment process in Parijoto fruit, extract is made by maceration using 96% ethanol solvent for several properties such as antioxidant, antidiabetic, antiacne, anticholesterol, antihyperlipidemia, antibacterial, anti-breast cancer and toxicity to improve public health in Indonesia. In this review, primary data searches are conducted online, in the form of national and international journals, books and ebooks. The results obtained from several journals and other sources can be seen in various kinds of pharmacological activities of the active substances contained in parijoto (Medinilla magnifica)